Direct Energy Deposited Cladded Material Characterization: Exploring Barkhausen Noise and Thermal Field with Parametric Simulation - Diwakar V.; Sharma A.; Yusufzai M.Z.K.; Vashista M. (My University, 2025)
Abstract: Direct energy deposition (DED) is a widely used manufacturing process for the production of high-performance metallic components. The process involves depositing a molten metal onto a substrate, which solidifies rapidly to form a clad layer. In this study, the effect of the DED-cladded material of SS316 on a Duplex SS was investigated using Barkhausen noise (BN) analyzer, and the BN signals was measured before and after the cladding process. The method is demonstrated to be effective in detecting microstructural changes, identifying defects, and evaluating the residual stress of the cladded material. The peak and RMS values of both cases exhibit an upward trend when the magnetizing frequency and magnetic field intensity are increased. There is a lower BN response appeared in the duplex SS compared to the cladded material, which gave direct information of the smaller grain size present in the duplex SS. The hysteresis loop characteristics, namely the average permeability, and remanence, showed an inverse relationship with respect to the low-frequency range. However, coercivity is directly proportional to all frequency ranges of the magnetizing waveform, whether it is a sine or triangular wave. The coercivity of the cladded material showed higher than the duplex SS, which is due to having a lower hardness level in the cladded material. Also, a parametric simulation is done to analyze the temperature distribution and heat affected zone (HAZ) at the interface of the deposited material and substrate. The results showed that at the higher value of the laser power, more HAZ appeared; however, as increasing the scanning speed, the HAZ values showed less at the constant value of laser power. The study provides valuable insights into the magnetic properties of cladded materials and their substrates, which can be used to evaluate material quality, hardness, and other mechanical properties. © Pleiades Publishing, Ltd. 2024. ISSN 1061-8309, Russian Journal of Nondestructive Testing, 2024, Vol. 60, No. 2, pp. 223–237. Pleiades Publishing, Ltd., 2024.